Glomerular variant of systemic amyloidosis in an Abyssinian cat Variante glomerular de amiloidosis sistémica en un gato Abisinio - Iregui, Carlos Arturo; Ávila, Jersson; Doncel, Benjamín; Ospina, Juan Carlos (Revista Colombiana de Ciencia Animal, 2015)
Amyloidosis is a disease in which a proteinaceous amorphous, eosinophilic, hyaline material is deposited extracellularly. A 4 year old Abyssinian male cat manifested disease; formalin fixed tissues were processed by the hematoxylin – eosin technique and submitted to histopathological examination. The clinical history included gastrointestinal signs, behavioral changes and poor body condition. In the histopathological evaluation an eosinophilic irregular-shaped extracellular material located in renal glomeruli, in the Dissé space of liver and around the glands in the large and small intestines. Affected tissues stained with Congo red revealed a material with green birefringence when examined under polarized light. Colonic ulcers, peritonitis and vasculitis were also seen and could be related to the pathogenesis of the amyloidosis in this case.